The Influence Of Use Of Canva Media On Students' Science Learning Outcomes Class X Tkj And Communication SMKS Muhammadiyah Sidenreng Rappang - Syamsunir, Syamsunir (La Ogi : English Language Journal, 2022)
This research uses quantitative methods and this type of experimental research which aims to test the effect of using Canva media on learning outcomes for students in class X TKJ and Communication at SMKS Muhammadiyah Sidenreng Rappang. The population in this study were all class X TKJ and Communication students Muhammadiyah Rappang Vocational School numbered 16 people and the sampling technique used was saturated sampling, so the sample in this study was 16 people. The independent variable in this research is the influence of using Canva media (x), while the dependent variable is the learning outcomes of class X TKJ and Communication students (y). This research was carried out in Muhammadiyah Sidenreng Rappang Vocational School. Data collection techniques use observation, documentation, and test Which Then analyzed using mean formula. Based on the results of data analysis, values are obtained X= 84 > value Y = 55 so it can be seen that there is an influence of using Canva media on students' science learning outcomes class X TKJ And Communication vocational school Muhammadiyah Sidenreng Rappang. The results of the research concluded that there was an influence of using Canva media on the science learning outcomes of class X TKJ and Communication SMKS Muhammadiyah Sidenreng Rappang students. This shows that the working hypothesis which states that there is an influence of the use of Canva media on the science learning outcomes of class X TKJ and Communication at SMKS Muhammadiyah Sidenreng Rappang, is accepted